Incidence of Lyme disease in the UK: a population-based cohort study - Victoria Cairns; Christopher Wallenhorst; Stephan Rietbrock; Carlos Martinez (BMJ Open)
Objectives The purpose of this study was to estimate the annual incidence of Lyme disease (LD) in the UK.Design This was a retrospective descriptive cohort study.Setting Study data were extracted from the Clinical Practice Research Datalink (CPRD), a primary care database covering about 8% of the population in the UK in 658 primary care practices.Participants Cohort of 8.4 million individuals registered with general practitioners with 52.4 million person-years of observation between 1 January 2001 and 31 December 2012.Primary and secondary outcome measures LD was identified from recorded medical codes, notes indicating LD, laboratory tests and use of specific antibiotics. Annual incidence rates and the estimated total number of LD cases were calculated separately for each UK region.Results The number of cases of LD increased rapidly over the years 2001 to 2012, leading to an estimated incidence rate of 12.1 (95% CI 11.1 to 13.2) per 100 000 individuals per year and a UK total of 7738 LD cases in 2012. LD was detected in every UK region with highest incidence rates and largest number of cases in Scotland followed by South West and South England. If the number of cases has continued to rise since the end of the study period, then the number in the UK in 2019 could be over 8000.Conclusions The incidence of LD is about threefold higher than previously estimated, and people are at risk throughout the UK. These results should lead to increased awareness of the need for preventive measures.Trial registration number This study was approved by the Independent Scientific Advisory Committee for CPRD research (Protocol number 13_210R).